Low‐molecular‐weight heparin biosimilars: potential implications for clinical practice. Issue 5 (May 2014) - Nandurkar, H.; Chong, B.; Salem, H.; Gallus, A.; Ferro, V.; McKinnon, R.
Abstract A working group of clinicians and scientists was formed to review the clinical considerations for use of low‐molecular‐weight heparin (LMWH) biosimilars. LMWH are biological molecules of significant complexity; the full complexity of chemical structure is still to be elucidated. LMWH biosimilars are products that are biologically similar to their reference product and rely on clinical data from a reference product to establish safety and efficacy. The complex nature of LMWH molecules means that it is uncertain whether a LMWH biosimilar is chemically identical to its reference product; this introduces the possibility of differences in activity and immunogenicity. The challenge for regulators and clinicians is to evaluate the level of evidence required to demonstrate that a LMWH is sufficiently similar to the reference product. The consensus opinion of the working group is that prior to clinical use a LMWH biosimilar should have proven efficacy and safety, similar to the reference product with prospective studies, which should be confirmed with a proactive post‐marketing pharmacovigilance programme.